Evaluation of the efficacy of a bioactive synthetic graft material in the treatment of intrabony periodontal defects - Vishakha Grover; Anoop Kapoor; Ranjan Malhotra; Ranjit Singh Uppal (Wolters Kluwer Medknow Publications, 2013)
Background: Bioactive ceramic fillers are synthetic materials which have shown the potential to enhance bone formation. The purpose of this study was to evaluate the efficacy of a bioactive synthetic graft material in the treatment of intrabony periodontal defects. Materials and Methods: Fourteen intrabony defects in twelve systemically healthy subjects having moderate to severe chronic periodontitis were evaluated after bone grafting with bioactive ceramic filler for a period of 6 months. Clinical and radiographic evaluations were made at baseline, at 3 and 6 months following surgery. Results: Mean radiographic defect fill of 64.76% (2.49±0.5 mm) was observed in 6 months, which was statistically significant. A statistically significant relative attachment level gain of 2.71±1.13 mm and probing pocket depth reduction of 4.21±1.18 mm was recorded at the end of the study. A significant decrease in mobility and gingival index was observed. Conclusions: Bioactive glass is an efficacious treatment option for the reconstruction of intrabony periodontal defects as it led to statistically significant improvements in the clinical and radiographic parameters.